PERAN KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI PADA PT.ASADA MITRA PACKINDO SENTUL-BALARAJA - Muhammad Saleh (LP2M Universitas Bina Bangsa, 2021)
The background of this study is the decrease in employee work productivity is caused by several factors and the most prominent factors are related to compensation and the work environment so that it impacts employee work productivity. This research aims to find out: (1) the role of compensation for the work productivity of employees of the production section at PT. Asada Mitra Packindo Sentul-Balaraja, (2) the role of the work environment on the work productivity of production employees at PT. Asada Mitra Packindo Sentul-Balaraja, (3) the role of compensation and work environment of work productivity of production employees at PT. Asada Mitra Packindo Sentul-Balaraja. This research uses descriptive research methods with quantitative approaches. The population in this study was the entire production section of 45 employees and a sample of 45 respondents. The data was collected with questionnaires that had been tested for validity and reliability. The data analysis technique used is multiple linear regression. The results showed that: compensation and work environment together play a role in the work productivity of employees in the Production section at PT. Asada Mitra Packindo with a calculated f value greater than ftable amounted to, 15,335> 3.22. Partially compensation plays a role in employee work productivity with a calculated value greater than ttable amounting to, 5.103 > 2.01808, while the work environment does not play an important role in employee work productivity because the valueof tcalculated is smaller than ttable amount, 1,088 < 2.01808. Therefore, this research can be concluded to increase employee work productivity, it is necessary to increase compensation as an appreciation of employee performance, in addition, the work environment needs to be improved to increase employee satisfaction which has an impact on employee productivity.